The secret soldier [compact disc, unabridged] - Berenson, Alex (Berenson, Alex. John Wells novel., 2011)
Entreated by the aging king of Saudi Arabia to infiltrate dark factions that are plotting against the monarchy, ex-CIA agent John Wells goes undercover only to learn of a massive conspiracy to trigger an ultimate confrontation between America and Islam.